2005
DOI: 10.1103/physrevb.72.235307
|View full text |Cite
|
Sign up to set email alerts
|

Transport between edge states in multilayer integer quantum Hall systems: Exact treatment of Coulomb interactions and disorder

Abstract: A set of stacked two-dimensional electron systems in a perpendicular magnetic field exhibits a three-dimensional version of the quantum Hall effect if interlayer tunneling is not too strong. When such a sample is in a quantum Hall plateau, the edge states of each layer combine to form a chiral metal at the sample surface. We study the interplay of interactions and disorder in transport properties of the chiral metal, in the regime of weak interlayer tunneling. Our starting point is a system without interlayer … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…On the experimental side, a number of experiments on 3D semiconductor multilayers have explored the behavior of stacked integer quantum Hall states [5,6,7], including the novel vertical transport due to the conducting surface sheath. [1,8,9,10,11,12,13,14] More recently, experiments on bismuth crystals in high magnetic fields have revealed intriguing anomalies in the ultra quantum limit -the limit where the magnetic field is sufficiently large that only the lowest Landau level is (partially) occupied. [15] It has been suggested that a novel 3D fractional quantum Hall type state might be present.…”
Section: Introductionmentioning
confidence: 99%
“…On the experimental side, a number of experiments on 3D semiconductor multilayers have explored the behavior of stacked integer quantum Hall states [5,6,7], including the novel vertical transport due to the conducting surface sheath. [1,8,9,10,11,12,13,14] More recently, experiments on bismuth crystals in high magnetic fields have revealed intriguing anomalies in the ultra quantum limit -the limit where the magnetic field is sufficiently large that only the lowest Landau level is (partially) occupied. [15] It has been suggested that a novel 3D fractional quantum Hall type state might be present.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to investigate the effect of surface disorder on the 2D chiral surface states. Theoretically, the disordered surface states have been mainly investigated using a 2D directed network model 4,[24][25][26][27]29 and a 2D continuum model [21][22][23][30][31][32] . However, we note that the scattering strength of an adatom on a sample surface can easily be the order of magnitude of 1 eV 33,34 , which can be much larger than the 3D quantum Hall gap 6 .…”
Section: Introductionmentioning
confidence: 99%